The structural-adjustment debate - Summers, Lawrence H.; Pritchett, Lant (American Economic Review, 1993)
The last decade has witnessed dramatic changes in economic policy in the developing world. On every continent, countries have moved to open their economies, free up prices, and reduce the role of the state in managing and regulating economic activity. Developing nations from Mexico to Malaysia have made changes in their economies that dwarf anything achieved by Ronald Reagan. The design of structural adjustment programs directed at the four ... ations-stabilization, liberalization, deregulation, privatization-has become a cottage industry. Efforts at structural adjustment have been assisted and encouraged by the international community, most directly through multilateral financial institutions. The International Monetary Fund has long conditioned its support on policies consistent with macroeconomic stability. The IMF has increasingly taken the position that changes in economic structure are necessary if stabilization is to be attained and maintained. Structural-adjustment lending (lending conditioned on specific economic policy changes) has emerged as a major instrument of World Bank support to developing countries, and World Bank investment lending has increasingly been conditioned on policy reforms. Given the extent of economic change that structural-adjustment programs have wrought, it is hardly surprising they have been controversial. This paper summarizes the results of the latest World Bank Review of Adjustment Lending (World Bank, 1992) and highlights the crucial identification problem involved in assessing structuraladjustment programs. We then try to advance the debate over structural-adjustment lending by distilling the main lines of criticism levied against structural-adjustment programs to four critiques and assessing the validity of each. In conclusion, we point to three newer issues for which we believe further research and analysis are necessary.